Effects of organic loading rate and hydraulic retention time on treatment of phenolic wastewater in an anaerobic immobilized fluidized bed reactor - Pishgar, Roya; Najafpour, Ghasem D.; Neya, Bahram Navayi; Mousavi, Naﬁse; Bakhshi, Zeinab (Journal of Environmental Engineering and Landscape Management, 2014)
Treatability of phenolic wastewater in an anaerobic immobilized fluidized bed reactor (AIFBR) in consequence of stepwise increment in phenolic load as well as decrease in hydraulic retention time (HRT) was investigated. The experimental data indicated that high degradation efficiencies of phenol and COD in the bioreactor at low HRTs and high organic loading rates were obtained. At constant HRT of 16 h with increase in influent phenol concentration from 98 to 630 mg/l, the average phenol and COD removals were 96 and 88%, respectively. However, further increase in phenol concentration in the feed stream to 995 mg/l resulted in decrease in phenol and COD removal efficiencies to 84 and 79%, respectively. For influent phenol concentration of 995 mg/l, the biogas production rate of 4.55 l/l.d was obtained. As HRT decreased from 3 to 0.15 day, the system showed high stability; influent phenol and COD were removed and reached to average values of 17 and 173 mg/l correspond to the removal efficiencies of about 97 and 90.5%, respectively. The bioreactor experienced a failure with further decrease in HRT to 0.1 day. Biogas production was gradually decreased from 7.04 l/l.d at HRT of 3 days to 2.23 l/l.d at HRT of 0.1 days. The value of the ratio of volatile fatty acids to total alkalinity (VFAs/TA) ranged from 0.03 to 0.24 during the entire course of operation.